ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK KONVENSIONAL DAN BANK SYARIAH - Isti Fadah; Tatok Endhiarto; Wahyu Andani; Ariwan Joko Nusbantoro; Sudarsih Sudarsih (Study Program of Management Faculty of Economics and Business University of Jember, 2022)
The study is a quantitative descriptive research using CAMEL research method approach and different test to compare financial performance of Bank Rakyat Indonesia and Bank Rakyat Indonesia Syariah. The population in this study is Bank Rakyat Indonesia and Bank Rakyat Indonesia Syariah of 2015 – 2019. The reason for choosing these years is because the researcher assess that these years are the newest years from previous years. Data type used in this study is secondary data which listed on Indonesia Stock Exchange (BEI) and obtained from www.idx.co.id and the official website of PT Bank Rakyat Indonesia Tbk or abbreviated as BRI and PT Bank Rakyat Indonesia Syariah or abbreviated as BRIS on 2015 – 2019.